Corporate Governance Practices and Firm Performance: A Study of Listed Companies in Sri Lanka - Sentheeswary, S. (My University, 2020)
Good corporate governance is necessary for all the business organizations because it plays an important role in the management of organizations in both developed and developing countries. The main objective of the study is to explore the efficacy of corporate governance practices, which affect firm performance. A survey was carried out on the 41 top listed companies in CSE during the period 2012 to 2017. Based on the research analysis using pooled OLS regression results, we conclude that corporate governance practices have a statistically significant and strong effect on the firm performance proxy by Tobin’s Q (model 01). Also, in model 02, this shows an insignificant impact between board composition, board size and firm performance. Further, this shows a negative significant impact between CEO duality on firm performance. Model 03, using ROA as dependent variable for the proxy to firm performance shows that there is a significant impact between board composition, CEO duality and no significant impact between board size and firm performance. This finding is confirmed by the p-value of the regression coefficient which is seen to be less than 0.05 (5%) 1evel of significance. It is estimated from the result that 1% increase in corporate governance practice on the average, will lead to 12% increase in TobinQ, 93.33% increase in ROE and 18.2% increase in ROA. The computed coepfficient of determination (0.12, 0.93 and 0.18) shows the proportion of variation in the corporate governance practices. Study brings out an increased understanding that there is significant impact between corporate governance practices and performance in listed companies in Sri Lanka.
Keywords: Corporate Governance; Firm Performance; Board Structure; Board composition; Board Size; Return on Equity; Return on Assets